Evaluation of Remodeling and Extrusion of Polyurethane Meniscal Implants after Meniscus Reconstruction using Ultrasonography - Poboży, Tomasz; Konarski, Wojciech; Poboży, Kamil; Domańska, Julia; Konarska, Klaudia (Current Medical Imaging, 2024)
Introduction:Meniscal tears are among the most common indications for knee arthroscopy. Artificial polyurethane scaffolds have demonstrated efficacy in reducing pain and promoting the growth of normal meniscal tissue, with high absorption rates facilitating full tissue regeneration.Aims:This study aimed to evaluate the remodeling of polyurethane meniscal implants post-reconstruction using ultrasonography. This imaging technique not only assesses changes in implant properties, such as echogenicity, but also the shape changes during functional examination.Methods:The assessment of meniscal extrusion, comparing size at rest and under weight-bearing, is an indirect parameter that provides insight into the physical properties of the remodeling implant, with greater extrusion indicating reduced stiffness and inferior physical properties of the meniscus. Ultrasonography has the valuable advantage of allowing for assessment of the blood supply to the meniscus through Power Doppler imaging.Results:The presence of vessels within the meniscal implants serves as evidence of ongoing remodeling. The study included 35 patients (13 female, 22 male; mean age 41.6 years, range 18-66) who underwent arthroscopic meniscal reconstruction with polyurethane implants, with an average time from surgery of 2.8 years (range 0.3-4.5 years). Results showed complete (29.7%), significant (45.9%), or moderate (16.2%) remodeling into natural meniscal tissue in 91.8% of the implants.Conclusion:The mean values of extrusion in the supine position and during 90-degree flexion were significantly greater in the operated limb (2.603) compared to the contralateral limb (1.978; t(35) = 2.442; P < 0.05). No significant differences in extrusion were found between the limbs in a standing position, indicating favorable physical properties of the polyurethane meniscal implants. Further ultrasonography studies of meniscal scaffolds are deemed relevant.
Keywords: Arthroscopic surgery